Effect of circuit training on physical fitness among fifth-grade male elementary school students - inda Lestari; Ewan Irawan; Nasrullah; Anas Ardiansyah; Andy Eddy (Universitas Suryakancana, 2026)
This study was motivated by the low level of physical fitness among elementary school students, which impacts their learning ability and participation in physical activities; therefore, effective teaching methods are needed, one of which is circuit training. This study aims to analyze the effect of the circuit training method on the physical fitness levels of fifth-grade students at SDN Inpres Sampungu. The study employed a quantitative approach using a quasi-experimental design with a one-group pretest–posttest design, involving a sample of 15 male students selected via purposive sampling. The instrument used was the Indonesian Physical Fitness Test (TKJI), which included a 40-meter run, pull-ups, sit-ups, vertical jump, and a 600-meter run, with circuit training administered over 8 sessions. The results of the study showed a significant increase in the average physical fitness score from 10.7 on the pretest to 20.1 on the posttest. The results of the paired sample t-test showed a t-value of -36.9 with a significance level of p < 0.001, indicating a highly significant difference between pre- and post-intervention scores. Thus, circuit training has been proven effective in significantly improving students’ physical fitness.